PADA SUATU KETIKA “REFLEKSI DIRI PADA MEMORI PENGALAMAN, DARI PAKSAAN HINGGA HASRAT BERKESENIAN” - CHRISNA BAYU SEPTRIANTO (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2017)
In life there must be a failure, success, pleasure, sorrow, such as there are black and white. These experiences create a mirror for us to appreciate the past, as a historical record that wraps paradigm and maturity to know the good and the bad. The tragedy that has teralami is a boon if we've experienced. Just like a fairy tale that gives grooved causal story, the story of the story gives the value of the policy will be what we will do and how we behave more positively like the proverbial what we plant is what we will harvest.